Application of OCT for osteonecrosis using an endoscopic probe based on an electrothermal MEMS scanning mirror. Issue 1 (1st January 2021) - Wang, D.; Zhang, J.; Liu, L.; Yan, Z.; Wang, P.; Ding, Y.; Xie, H.
Abstract: Osteonecrosis becomes a more widespread problem as the population is getting older. Current osteonecrosis diagnosis not only requires invasive procedures but also often leads to surgical replacement. This paper reports a preliminary study of applying optical coherence tomography (OCT) for noninvasive diagnosis of osteonecrosis using an endoscopic probe based on a microelectromechanical (MEMS) scanning mirror. The endoscopic MEMS probe is only 2.5 mm in diameter and can scan a field of view of 24°. First a tissue sample of femoral head with osteonecrosis is scanned with the MEMS probe. The resultant OCT images can clearly delineate the necrosis region from the normal bone. Then in vivo experiments are carried out on an adult rabbit, in which the rabbit's femoral head is scanned and imaged with the same MEMS probe and both three-dimensional (3 D) structural images and blood flows are obtained. The OCT imaging experiments show that the femoral head of this rabbit does not have osteonecrosis and its blood flow is present, which is in agreement with the destructive diagnosis. The blood flow rates in the femoral head are extracted from the OCT images acquired in three cases: normal blood supply, partial ischemia and complete ischemia, which are 19.3 mm/s, 11.9 mm/s, and 1.88 mm/s, respectively. These experiments demonstrate that OCT can clearly distinguish between the osteonecrosis and normal bone and measure the blood flow rate in the bone, both with the cartilage present, showing great potential for non-invasive osteonecrosis diagnosis.